A Systematic Literature Review Of Mental Health Diagnostic Using K-Nearest Neighbour - Whale Optimization Algorithm - Septian, Firza; Kusrini , Kusrini; Hidayat, Tonny (Universitas Lembah Dempo, 2023)
People including unborn infants are negatively impacted by a number of things, such as noise. Noise and the others aspect could affect somebody mental health. Mental health as natural problem might be easier detected using metaheuristic algorithm, K-Nearest Neighbour - Whale Optimization Algorithm (KNN-WOA) is one of them. A variety of trustworthy sources, including IEEE and Scopus, are used to collect the data. In the action research technique, practical applications work as a